Pengelolaan Personal Branding Gamaliel Tapiheru Melalui Media Sosial Instagram - Saragih, Elvan Adventri (Brand Communication, 2024)
Personal Branding is the way people shape themselves as they want to be seen by others. Gamaliel is a musician who made his debut as a professional musician with his music group "GAC". Every person has their own way to manage their personal branding depend on the preferences they have. The researcher find that Gamal’s personal branding is interesting to discuss because of the unity of his social media and his music he create. The researcher uses the Theory of 8 Elements of Montoya's Personal Branding as the main theory in this research with semi-structured interview data collection techniques.